ANALISIS FAKTOR YANG MEMPENGARUHI VOLUME IMPOR DAN PRODUKSI BAWANG PUTIH DI INDONESIA - Meleriansyah, Meleriansyah; Iskandar, Sutarmo; Kurniawan, Rahmat (Universitas Muhammadiyah Palembang, 2014)
This study aims to determine how to factor in the price of imported garlic, gross domestic product and the production of garlic in indonesia which affects the volume of imported garlic, and to find out how the acreage factor, interest rates and the level of labor costs that affect garlic production in indonesia. The research was carried by talking secondary data about garlic BPS Indonesia and relevant agencies. Time data collection carried out in December 2013 - February 2014. The method used is the method of data used are secondary data straight time (time series). Processing and dat analysis method affect the volume of imports and garlic production in indonesia using multiple linear regression analysis. The results of the study showed that the price of imported garlic, gross domestic product and the production of a significant effect on the volume of imported garlic in Indonesia. As for the area of a significant effect on the production of garlic, while interest rates and labor costs will be non-significant effect on the production of garlic.